Effect of different dielectric drying methods on the physic-chemical properties of a starch-water model system - Jiang, H.; Zhang, M.; Fang, Zhongxiang; Mujumdar, A.; Xu, B. (Elsevier, 2016)
To investigate the structure and morphological characteristics of potato starch-water model starch system dried under dielectric field of different wave length (included 27, 915 and 2450 MHz). The ratio of amylose/amylopectin content, molecular mass (Mw), degree of crystallinity and surface morphology were determined. The results indicated that the starch crystalline changed from type A to type B, and the crystallinity increased upon the dielectric drying. The Mw of dried starch was ranged from 1.532 × 107 to 2.059 × 107 and the ratio of higher degree of polymerization (>150) varied from 20.57% to 6.87% (27 MHz), 0% (915 MHz) and 0% (2450 MHz). These Mw and degree of polymerization variations resulted in the lower viscosity but higher pasting temperature of the dried starch. However, the dried starch was still able to gelatinize and this was observed under the SEM imagines. The dielectric properties and drying dynamic of dried starch showed the interaction with the dielectric frequency.